THE IMPORTANCE OF ENRICHING THE CREATIVE IMAGINATION OF ELEMENTARY SCHOOL STUDENTS - Sayyora Askarbekovna, Matkarimova (Recent scientific discoveries and methodological research, 2024)
Creative imagination is a fundamental aspect of childhood development, influencing cognitive growth, problem-solving abilities, and emotional resilience. This article examines the critical role of fostering creativity in elementary school students, focusing on how imaginative activities contribute to holistic development. The discussion includes theoretical underpinnings, practical classroom strategies, and challenges educators face. The conclusion underscores the long-term benefits of nurturing creativity, emphasizing its role in preparing students for an innovative and dynamic future.